A Rodential Reckoning: A Case Report and Systematic Review of Streptobacillary Endocarditis - Ashwin Mahesh; Eduardo Messias Hirano Padrao; Ravneet Randhawa; Christi Oommen; Johanna Romo; Ramachandra Illindala; Henry Anyimadu (Autopsy and Case Reports, 2023)
Introduction: Endocarditis is a rare, often fatal complication of rat bite fever caused by Streptobacillus moniliformis. Only 39 cases have been reported (including this case) as of 2022. We describe a case and aim to perform this entity’s first systematic literature review. Methods: We performed a systematic review in CENTRAL, EMBASE, MEDLINE, SciELO, and LILACS. The terms used were terms used were (but not limited to) rat bite fever, Streptobacillus moniliformis, Spirillum minus, and endocarditis. We included all abstracts and articles with patients with echocardiographic or histologicproven endocarditis. In case of discordance, a third reviewer was involved. Our protocol was submitted to PROSPERO (CRD42022334092). We also performed searches for studies on the reference list of included articles. Results: We retrieved 108 and included 36 abstracts and articles. A total of 39 patients (including our report) were identified. The mean age was 41.27, and 61.5% were males. The most common findings were fever, murmur, arthralgias, fatigue, splenomegaly, and rash. Underlying heart disease was present in 33%. Exposure to rats was noted in 71.8% of patients, with 56.4% recalling a rat bite. Anemia was seen in 57%, leukocytosis in 52%, and elevated inflammatory markers in 58% that had lab work performed. The mitral valve was most affected, followed by the aortic, tricuspid, and pulmonary valves. Surgical intervention was required in 14 (36%) cases. Of those, 10 required valve replacement. Death was reported in 36% of cases. Unfortunately, the literature available is limited to case series and reports. Conclusion: Our review allows clinicians to suspect better, diagnose, and manage Streptobacillary endocarditis.